2007
DOI: 10.1007/s10529-007-9376-8
|View full text |Cite
|
Sign up to set email alerts
|

A novel binary expression vector for production of human IL-10 in Escherichia coli and Bifidobacterium longum

Abstract: A novel expression vector (pLR) driven by hup promoter and Bifidobacterium beta-galactosidase signal peptide was constructed. The pLR vector was used for the expression of the optimized human IL-10 synthetic gene in Escherichia coli and Bifidobacterium longum. In both microorganisms, rhIL-10 was in a soluble form in total extract cells. The recombinant hIL-10 was partially processed in E. coli, whereas in Bifidobacterium all rhIL-10 was found in the mature form.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 11 publications
2
16
0
Order By: Relevance
“…The amyB signal peptide (Chenoll et al, 2015) was fused in frame with the a-MSH gene to facilitate the secretion of a-MSH from the cells. An oligonucleotide carrying a fusion of RBS, the amyB signal sequence and the a-MSH gene was synthesized using codon optimization for bifidobacteria (Reyes Escogido et al, 2007). To utilize the signal peptides, we designed two plasmids, pDGMSH1 and pDGMSH2, which consisted of signal peptides with different lengths, with the predicted amino acid sequences shown in Table 2.…”
Section: Vector Constructionmentioning
confidence: 99%
“…The amyB signal peptide (Chenoll et al, 2015) was fused in frame with the a-MSH gene to facilitate the secretion of a-MSH from the cells. An oligonucleotide carrying a fusion of RBS, the amyB signal sequence and the a-MSH gene was synthesized using codon optimization for bifidobacteria (Reyes Escogido et al, 2007). To utilize the signal peptides, we designed two plasmids, pDGMSH1 and pDGMSH2, which consisted of signal peptides with different lengths, with the predicted amino acid sequences shown in Table 2.…”
Section: Vector Constructionmentioning
confidence: 99%
“…Another bifidobacterial expression vector system utilized the hup (histone-like protein) gene promoter and was used to express cytosine deaminase in B. longum (202), human interleukin-10 (IL-10) in B. longum (86), the Salmonella flagellin gene in B. animalis (304), and human basic fibroblast growth factor (FGF-2) in B. breve (286). The expression of cytosine deaminase in B. longum was used to treat hypoxic tumors in mice, as previous studies had indicated that bifidobacteria selectively localized only in hypoxic tumor cells, not normal cells, pointing to the tumor-targeting properties of bifidobacteria (56,165,349,350).…”
Section: Development Of Cloning and Expression Vector Systems For Bifmentioning
confidence: 99%
“…Nevertheless, successful use of the P BAD system in bifidobacteria suggests that at least some E. coli promoters are recognized by the transcription machinery of bifidobacteria. This is supported by the use of the T5 phage promoter for recombinant protein expression in bifidobacteria (25,42) and P hup for expression of a codonoptimized human interleukin 10 gene in both E. coli and B. longum (68).…”
Section: Inducible Promotersmentioning
confidence: 99%
“…class II bacteriocin pediocin PA-1 in B. longum MG1, and the recombinant protein was found in the supernatants of the recombinant strain and was active against Lactobacillus plantarum and Listeria monocytogenes (52). The signal peptide of the ␤-galactosidase was successfully used for secretion of human interleukin 10 by B. longum (68). A series of expression vectors carrying the B. breve Sec2 signal peptide was constructed.…”
Section: Localization Signalsmentioning
confidence: 99%